Kinerja Penyuluh Pertanian pada Petani Padi Sawah di Desa Margacinta Kecamatan Moramo Kabupaten Konawe Selatan - Nalefo, La; Isnian, Sitti Nur; Ubaidillah, Fachrul Mu’alif (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This research department has a number of advantages, even though it has received assistance from extension workers, so the purpose of this the study of the performance of agricultural extension services on rice farmers. This research was conducted in April 2018 using quantitative research, which uses data that is described as qualitatively descriptive which is the study of the subject and object that has been determined. While collecting data is a questionnaire. The population in this study are agricultural extension agents and all farmers who are members of Gapoktan. The sampling technique was carried out in a simple random sampling method with a total sample of 56 farmers and 1 agricultural instructor. Analysis of the data used in agricultural instructors on farmer lowland rice using a percentage formula. The results showed that: The performance of agricultural extension workers in Margacinta Village, Moramo District, South Konawe District.